2023
DOI: 10.3390/cancers15072025
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, Prognosis, and Treatment of Canine Hemangiosarcoma: A Review Based on a Consensus Organized by the Brazilian Association of Veterinary Oncology, ABROVET

Abstract: Hemangiosarcoma is a mesenchymal neoplasm originating in the endothelial cells of blood vessels; they can be classified as non-visceral and visceral types. Non-visceral hemangiosarcomas can affect the skin, subcutaneous tissues, and muscle tissues; visceral hemangiosarcomas can affect the spleen, liver, heart, lungs, kidneys, oral cavity, bones, bladder, uterus, tongue, and retroperitoneum. Among domestic species, dogs are most affected by cutaneous HSA. Cutaneous HSA represents approximately 14% of all HSA di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 211 publications
2
5
0
Order By: Relevance
“…No predilection by sex has been described in the literature for the different splenic lesions in dogs [ 8 ]. However, some studies have shown a higher proportion of affected males than females [ 1 , 5 , 27 , 33 ], which coincides with the results of the present study, in which males showed an increased risk of developing splenic neoplasia. In this regard, it has been described that late-castrated females have a higher risk of developing tumors such as hemangiosarcoma and mast cell tumors than reproductively intact individuals [ 35 , 36 ], which suggests a possible protective role of estradiol [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…No predilection by sex has been described in the literature for the different splenic lesions in dogs [ 8 ]. However, some studies have shown a higher proportion of affected males than females [ 1 , 5 , 27 , 33 ], which coincides with the results of the present study, in which males showed an increased risk of developing splenic neoplasia. In this regard, it has been described that late-castrated females have a higher risk of developing tumors such as hemangiosarcoma and mast cell tumors than reproductively intact individuals [ 35 , 36 ], which suggests a possible protective role of estradiol [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…This result is not under what is recommended by the current literature, where it is suggested to send the complete spleen to analyze at least five different histopathological sections and thus maximize the probability of detection of splenic neoplasia, especially in the context of a diagnosis of hemangiosarcoma [ 24 ]. Hemangiosarcoma is the most common malignancy located in the spleen and has a poor prognosis due to the high risk of developing metastasis [ 5 ]. It originates from pluripotent bone marrow cells in a pre-differentiation state that migrate to highly vascularized sites, where they undergo malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main haematological findings associated with cardiac hemangiosarcoma are leukocytosis with a left shift, anaemia (regenerative or non-regenerative) with the presence of schistocytes and acanthocytes, microangiopathic damage, vasculitis and acute haemorrhage. 19 In the case described, there was a severe non-regenerative anaemia present. Splenic hemangiosarcoma is associated with a paraneoplastic microangiopathic haemolytic anaemia that can occur secondary to erythrocyte damage due to abnormal tumour vascularity.…”
Section: Discussionmentioning
confidence: 80%